2019
DOI: 10.1002/jbm.a.36606
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional graphene oxide‐reinforced porous biodegradable polymeric nanocomposites for bone tissue engineering

Abstract: This study investigates the mechanical properties and in vitro cytotoxicity of two‐dimensional (2D) graphene oxide nanoribbons and nanoplatelets (GONRs and GONPs) reinforced porous polymeric nanocomposites. Highly porous poly(propylene fumarate) (PPF) nanocomposites were prepared by dispersing 0.2 wt % single‐ and multiwalled SONRs (SWGONRs and MWGONRs) and GONPs. The mechanical properties of scaffolds were characterized using compression testing and in vitro cytocompatibility was assessed using QuantiFlour as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The developed composites showed excellent features in terms of thermal stability, mechanical performance, water absorption, hydrophilicity, hydrolytic degradation, protein absorption capability, cytotoxicity viscoelastic, and antibacterial properties. In addition, cell viability experiments have been performed, demonstrating that PPF/PEG-GO nanocomposites do not lead to toxic effects on normal human dermal fibroblasts (NHDF) and other cell types, suggesting, so far, a considerable potential for medical utilization, principally for bone tissue engineering applications [ 40 , 41 , 42 , 43 ].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…The developed composites showed excellent features in terms of thermal stability, mechanical performance, water absorption, hydrophilicity, hydrolytic degradation, protein absorption capability, cytotoxicity viscoelastic, and antibacterial properties. In addition, cell viability experiments have been performed, demonstrating that PPF/PEG-GO nanocomposites do not lead to toxic effects on normal human dermal fibroblasts (NHDF) and other cell types, suggesting, so far, a considerable potential for medical utilization, principally for bone tissue engineering applications [ 40 , 41 , 42 , 43 ].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Some investigators have reported that GO and its compounds are biocompatible and could guide stem cells to promote proliferation and osteoblast differentiation (Xie, Cao, Rodriguez‐Lozano, Luong‐Van, & Rosa, ). In our previous work, we demonstrated that pristine GO nanoparticles could promote osteogenic differentiation in BMSCs and that 0.1 μg/ml was the most suitable concentration (Farshid et al, ; Wei et al, ). However, the osteogenic effect of GO was limited, and toxicity existed.…”
Section: Introductionmentioning
confidence: 99%
“…The development of new scaffold materials with improved mechanical properties and biodegradability is of great importance in the field of tissue engineering. Until now, both inorganic and organic materials were investigated, and biodegradable synthetic polymers emerged as the most promising candidates for orthopedic applications 1,2 . Poly(propylene fumarate) (PPF) is an unsaturated linear polyester that can be easily crosslinked either thermally or with photoinitiators 35 .…”
Section: Introductionmentioning
confidence: 99%